Epstein–Barr virus infection in children with renal transplantation: 17 years experience at a single center. (June 2014) - Comak, Elif; Akman, Sema; Ongut, Gozde; Colak, Dilek; Koyun, Mustafa; Dogan, Cagla Serpil; Mutlu, Derya; Saglik, Imran; Gokceoglu, Arife Uslu; Dinckan, Ayhan
Abstract Objectives: The aim of this study was to detect the frequency, time of occurrence, management and outcome of Epstein–Barr virus (EBV) infection and related complications in pediatric renal transplant recipients. Methods: Pediatric renal allograft recipients transplanted between August 1994 and December 2011 at our hospital was evaluated retrospectively. The patients were divided into two groups; Groups 1 and 2 were composed of patients transplanted before and after November 2007, respectively, when plasma EBV DNA levels were periodically measured. Results: The study included 166 children, 89 (53.6%) boys, with a mean age of 12.2 ± 3.8 years. Prior to transplantation, 144 patients (86.7%) were EBV seropositive. Within a median follow-up period of 36 months, 11 of 22 seronegative children (50%) developed primary EBV infection. EBV reactivation was observed in 23 of 144 children (15.9%). Two patients with primary infection developed post-transplant lymphoproliferative disorder, one of whom died. Elevated serum creatinine levels or graft loss were not observed in any patient with EBV reactivation. Conclusions: EBV DNA monitoring by PCR in high-risk pediatric renal transplant recipients will provide early diagnosis and treatment of EBV infections.